The effects of partial replacement of fishmeal protein by hydrolysed feather meal protein in the diet with high inclusion of plant protein on growth performance, fillet quality and physiological parameters of Pengze crucian carp (Carassius auratus var. Pengze). (26th November 2019) - Yu, Ruihe; Cao, Hongzhong; Huang, Yaying; Peng, Mo; Kajbaf, Kimia; Kumar, Vikas; Tao, Zhiying; Yang, Gang; Wen, Chungen
Abstract: Goal of this research is to explore the effects of graded dietary levels of hydrolysed feather meal (HFM) protein as an alternative of fishmeal protein on Pengze crucian carp ( Carassius auratus var. Pengze). Five isonitrogenous (35% crude protein) diets were formulated as Control diet and four other diets F15, F30, F45 and F60 wherein 15%, 30%, 45% and 60% fishmeal protein replaced by HFM protein fed for 70 days. The results showed that fish growth was unaffected up to 45% fishmeal protein replacement. Dietary HFM protein could reduce the crude protein composition of body and further affect fillet quality through a significant increase in springiness, gumminess, chewiness and/or resilience. Activity of digestive enzymes (amylase, lipase and tryptase) increased as the fishmeal protein replacement increased, whereas a higher replacement level had negative impacts on absorptive capacity of intestine by decreasing its absorptive area, following by a reduction in concentration of lactate dehydrogenase, total cholesterol, high‐density lipoprotein, low‐density lipoprotein and ammonia in serum. Although intestinal antioxidant parameters were elevated by dietary HFM protein, the content of malondialdehyde in intestine was also positively associated with the protein replacement level. Overall, our results indicate that up to 45% of fishmeal protein could be replaced by HFM protein in diet without significant impact on the growth of Pengze crucian carp, whereas the crude protein content of whole body, fillet quality and oxidative status would significantly be affected when the replacement level of fishmeal protein reaches 30% together with a negative effect on the intestinal histology.